2020
DOI: 10.1186/s12913-020-05664-x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence, adherence, healthcare resource utilisation and costs for interferon Beta in multiple sclerosis: a population-based study in the Campania region (southern Italy)

Abstract: Background: To differentiate five formulations of Interferon Beta for the treatment of multiple sclerosis (MS) in clinical practice, by analysing persistence, adherence, healthcare resource utilisation and costs at population level. Methods: In this population-based study, we included individuals with MS living in the Campania Region of Italy from 2015 to 2017, on treatment with intramuscular Interferon Beta-1a (Avonex® = 618), subcutaneous pegylated Interferon Beta-1a (Plegridy® = 259), subcutaneous Interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 44 publications
(72 reference statements)
5
15
1
Order By: Relevance
“…Adherence of about 93% is in agreement with previously reported adherence rates to subcutaneous interferon beta therapy >90% ( 23 25 ) with a higher adherence of Peg IFN beta-1a compared with other subcutaneous interferons ( 26 ). However, the relatively small sample size and the short follow-up are likely to affect the comparison with data from other IFN-beta studies with longer duration and more participants.…”
Section: Discussionsupporting
confidence: 91%
“…Adherence of about 93% is in agreement with previously reported adherence rates to subcutaneous interferon beta therapy >90% ( 23 25 ) with a higher adherence of Peg IFN beta-1a compared with other subcutaneous interferons ( 26 ). However, the relatively small sample size and the short follow-up are likely to affect the comparison with data from other IFN-beta studies with longer duration and more participants.…”
Section: Discussionsupporting
confidence: 91%
“…Incremental costs were primarily driven by pharmacy costs in patients in the NR and MMR cohorts, whereas medical costs were the key drivers in patients in the SR cohort. These observations are in line with previous long-term observational studies that speculated the costs of DMTs to be important predictors of the increased cost burden [ 10 , 11 ]. We observed that patients with severe relapses incur a high cost burden, which underscores the need to prevent progression.…”
Section: Discussionsupporting
confidence: 91%
“…The disease-modifying therapies (DMTs) were invented to reduce the relapse rates, delay disease progression, and reduce future disability in patients with RRMS [ 5 , 9 ]. However, switching among the first-line DMTs is common and is an important predictor of economic burden in patients with MS [ 10 , 11 ]. Moreover, the use of high-efficacy (and costly) DMTs could prevent relapses and delay disease progression leading to savings in overall costs [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-adherence to DMTs is common, and is associated with higher risk of relapses and disability progression [ 81 , 82 , 83 ]. However, interventions to foster adherence in MS are costly, time-consuming, and difficult to evaluate in clinical practice [ 84 , 85 ]. Different studies have applied digital technology to auto-injectors [ 59 , 65 ], needle disposal systems [ 63 ], pill bottles [ 70 ], and diaries for monitoring DMT usage, adherence, and side effects [ 60 , 64 ].…”
Section: Discussionmentioning
confidence: 99%